Investigation of cytolethal distending toxin production and virulence genes in Campylobacter isolates from cattle - Acik, M. N.; Karahan, M.; Ongor, H.; Karagulle, B.; Cetinkaya, B. (Ecole Nationale Veterinaire Toulouse, 2013)
The prevalence of virulence and cytolethal distending toxin (Cdt) genes was investigated in isolates of Campylobacter jejuni, C. coli, C. lanienae and C. lari originated from intestinal contents and gall bladders of clinically healthy cattle. In this study the presence of 10 pathogenic genes responsible for the expression of adherence, invasion, colonization and cytotoxin production was examined in 210 Campylobacter species (194 C. jejuni, 12 C. coli, 3 C. lari, one C. lanienae) isolated from cattle intestinal content and gall bladder. In addition, Campylobacter isolates were investigated for production of functional cytolethal distending toxin (cdt) using HeLa cell culture. The presence of flaA (100%), cadF (96.7%), virB11(14.8%), pldA(39%), ciaB(30), dnaJ (61%), racR (63.8%), cdtA (70.5%), cdtb (70.9%) and cdtC (71.9%) genes was detected in Campylobacter species by PCR. Only three Campylobacter strains produced cytolethal distending toxin in a HeLa cell assay. These data suggest that all 10 virulence genes are widespread among Campylobacter isolates, but that capacity of cdt production are low in HeLa cell culture. To the authors'knowledge, this is the first study which reports the presence of virulence and toxin genes in C. lanienae isolated from cattle in the world.
Keywords: Campylobacter; cattle; cdt; virulence genes; HeLa cell culture